Research on relative age in Hungarian swimming - Nagy, N.; Ökrös, C.; Sos, C. (Physical Culture and Sport. Studies and Research, 2015)
In 2017, the 19th World Swimming Championship will be organized in Hungary. Up to now, many people have already been working with swimmers to achieve good results. However, in the next period they must work even harder to ensure that the national swimmers of a country as small as Hungary can achieve the outstanding results of their predecessors. Since high-level competitions in swimming have become more intense, innovations including scientific studies are needed during preparation for the event. The purpose of this paper is to present the major results of an independent study carried out by the authors about the relative age of the best Hungarian swimmers with the aim of contributing to their preparation. The research population consisted of selected age groups of swimmers registered by the Hungarian Swimming Association (N=400). The method for data collection was an analysis of documents. To evaluate the data, the Chi-square and Kruskal-Wallis tests were used. The results are presented according to the period of the competitor`s date of birth, gender, and age group. The results confirm only partly the hypothesis that people born in the first quarters of the year play a dominant role in Hungarian national swimming teams. In the conclusion, the authors recommend further research on relative age in swimming and in other sports.